Role of Independent Directors in the Changing Business Scenario in India (International Journal of Scientific Research and Management (IJSRM), 2016)
The literature on corporate governance and various codes emphasis that the Board of directors should provide direction to the company, evaluate and approve strategies, appoint and remove the chief executive officer and decide the compensation for him and other members of the top management. While an Independent Director should focus on the adequacy and effectiveness of the internal control and risk management systems, they are expected to protect the interest of non-controlling shareholders, should be watchful to identify weaknesses and should act tough only when required. Despite Enron, World Com and Satyam’s Boards having many Independent Directors , their presence could not avert the major corporate disasters. The challenges of Independent Directors are many folds and growing day by day. The government expects Independent Directors to bring an independent judgment to bear on the Board’s deliberations especially on the issue of strategy, performance; risk management, resources, key appointments and standards of conduct and bring an objective view in the evaluation of performance of Board and management. The public outrage in many corporate failures suggests that there is a huge expectation gap between what Independent Directors can do and what stakeholders expect to do. This gap is created because all the stakeholders have hyped the role of Independent Directors under the code of corporate governance. In order to be effective, they need to understand they can effectively protect the interest of non-controlling shareholders even when the Board is devoid of certain critical responsibilities. This paper attempts to find out "the ultimate measure of Independent Directors not where they stand in moments of comfort, but where they actually stand and should stand at the time of challenges and controversy."